F-18 FDG PET-CT in a Case of Unsuspected Bilateral Adrenal Histoplasmosis - M, Thanuja; M, Fazarina; CH, Ding (IIUM Medical Journal Malaysia, 2021)
Histoplasmosis is a common fungal infection in endemic countries including Malaysia. Although it is commonly diagnosed in immunosuppressed individuals, there is a preponderance of immunocompetent individuals among individuals with disseminated disease involving adrenal gland. There is a diagnostic dilemma in most patients as the clinical presentation, biochemical parameters and imaging features are frequently non-specific. On 18F-FDG PETCT, histoplasmosis shows high FDG avidity. However, due to overlapping features with other disease conditions, tissue biopsy remains as the confirmatory test. In this report, we present a case of disseminated histoplasmosis with high FDG uptake in the adrenal glands and lymph nodes which mimic a metastatic cancer.